The role of the ambassador of The BKKBN planning generation in socializing the Family Planning Program in North Sumatera - Khairina, Suci Ledian; Saleh, Arifin (COMMICAST, 2022)
Indonesia is an equatorial country which has a high population density. Data from the Central Bureau of Statistics in 2010 stated that of the total population of 237.6 million, including teenagers aged 10-24 years as much as 27.6 percent. The number of Indonesian adolescents based on the projection of Indonesia's population from 2010 to 2035 in 2018 will reach around 66.3 million (25.6%) of the total population. Based on this, the government must try to control the very high population growth rate. In this study, the authors used a qualitative descriptive research method. The results of the research are the role of an ambassador for the planning generation in disseminating the BKKBN program to the community, especially to adolescents in North Sumatra in order to prepare family life for adolescents to realize a prosperous family, then the target material that must be conveyed by the ambassadors for the planning generation is adolescent reproductive health, PKBR (Preparation of Family Planning for Youth), Life Skill, GenRe Program, Population, and other materials related to the BKKBN program. to the ambassador to maximize the targets and vision and mission to be achieved. In the aspect of completeness of information, it needs to be evaluated in order to provide the information needed by adolescents so that they still get mutual support to achieve the target of holding a periodic evaluation activity to measure the success of achieving their targets.Â Â